2012
DOI: 10.3140/bull.geosci.1351
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact on ectocochleate cephalopod reproductive strategies and the evolutionary significance of cephalopod egg size

Abstract: Published data on initial chamber (protoconch) diameter in 507 species, and embryonic shell (ammonitella) diameter in 231 species of Ammonoidea, and embryonic shell (nauta) diameters for 132 species of coiled Nautiloidea, were used to examine evolutionary change in ectocochleate cephalopod reproductive strategies. Palaeotemperatures were found to be a key factor influencing historical changes in the evolution of egg size in ammonoids and nautiloids. A negative relationship was found between egg size and warmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…After that stage, a change in ornamentation and shape occured (Currie 1942(Currie , 1944Burnaby 1966, Lehmann 1966Kulicki 1974Kulicki , 1979Kulicki , 1996Bandel et al 1982;Ward and Bandel 1987;Landman 1987, Landman et al 1996b, 2007aMaeda 1993;Kulicki and Doguzhaeva 1994;Bucher et al 1996;Doguzhaeva 2002;Kulicki et al 2002;Sprey 2002;Korn and Klug 2007;Tanabe et al 2010b). The corresponding term in nautiloids is nauta (Laptikhovsky et al 2013). According to Laptikhovsky et al (2013), the average ammonitella diameter was 0.54-2.6 mm, decreasing in mean size from the Devonian (up to > 5 mm; De Baets et al 2015) via the Carboniferous with 0.6-1.4 mm to the latest Cretaceous with 0.7-1.0 mm.…”
Section: Ontogenetic Stages In Ammonoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…After that stage, a change in ornamentation and shape occured (Currie 1942(Currie , 1944Burnaby 1966, Lehmann 1966Kulicki 1974Kulicki , 1979Kulicki , 1996Bandel et al 1982;Ward and Bandel 1987;Landman 1987, Landman et al 1996b, 2007aMaeda 1993;Kulicki and Doguzhaeva 1994;Bucher et al 1996;Doguzhaeva 2002;Kulicki et al 2002;Sprey 2002;Korn and Klug 2007;Tanabe et al 2010b). The corresponding term in nautiloids is nauta (Laptikhovsky et al 2013). According to Laptikhovsky et al (2013), the average ammonitella diameter was 0.54-2.6 mm, decreasing in mean size from the Devonian (up to > 5 mm; De Baets et al 2015) via the Carboniferous with 0.6-1.4 mm to the latest Cretaceous with 0.7-1.0 mm.…”
Section: Ontogenetic Stages In Ammonoidsmentioning
confidence: 99%
“…The corresponding term in nautiloids is nauta (Laptikhovsky et al 2013). According to Laptikhovsky et al (2013), the average ammonitella diameter was 0.54-2.6 mm, decreasing in mean size from the Devonian (up to > 5 mm; De Baets et al 2015) via the Carboniferous with 0.6-1.4 mm to the latest Cretaceous with 0.7-1.0 mm. Laptikhovsky et al (2013) concluded that seawater temperatures were the key factor provoking historical changes in ammonoid and nautiloid evolution.…”
Section: Ontogenetic Stages In Ammonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…A negative relationship between egg size and environmental temperature is known from extant cephalopods and has been reported both within species and between species (e.g., Laptikhovsky 2006). Latitudinal temperature-related differences in embryonic shell size might also have been present in ammonoids (Laptikhovsky et al 2013), but so far, the fossil record is spatially too patchy to test geographic differences in contemporary populations of the same species over large latitudinal distances, where this could be relevant (Tajika and Wani 2011). In extant cephalopods, there is also a large intrinsic variation at hatching at the same locality , which might also contribute to the large intraspecific variation reported in various ammonoids sampled from restricted intervals in time and space from the Paleozoic (Erben 1950(Erben , 1964Tanabe et al 1995;Stephen and Stanton 2002) to the Mesozoic (Tanabe 1977a, b;Landman 1987;Rouget and Neige 2001;Tanabe et al 2003;Tajika and Wani 2011).…”
Section: Size-at-age Variation In Ammonoidsmentioning
confidence: 99%
“…According to Thorson (1961) or Jablonski & Lutz (1980) about 65-70% the Recent species of bivalves have planktotrophic larvae and this type of larva permits the dispersion over the large distances. Babin (1995) and Sánchez & Babin (2003) presumed that all the Ordovician bivalves had the lecithotrophic larvae and this could explain the spatial restriction for the Ordovician bivalve genera (for early ontogenetic strategies in other molluscs, see Nützel & Frýda 2003, Manda 2008b, Klug et al 2010, Manda & Frýda 2010, Laptikhovsky et al 2013. Thorson (1961) studied the length of pelagic larval life in Recent marine invertebrates (including bivalves) and the larval transport by ocean currents.…”
Section: Diversification and Paleobiogeography Of Bivalves During Thementioning
confidence: 99%